Implementasi Tri Hita Karana Sebagai Budaya Organisasi di The Royal Pita Maha Hotel - Ni Putu Yunita Anggreswari; A. A. N. Oka Suryadinatha Gorda (Kamaya: Jurnal Ilmu Agama, 2020)
Tri Hita Karana is a Hindu concept that has the understanding of the three causes of human welfare consisting of three elements which include Parhyangan, namely the Godhead, the Pawongan element of Humanity and the Palemahan the environmental elements. Tri Hita Karana is treated as an organizational culture in The Royal Pita Maha Hotel which is then applied by all members of the organization as a standard of behavior. The formulation of the problem in this study is "How is the implementation of Tri Hita Karana as organizational culture at The Royal Pita Maha Hotel?". The research methodology in this research is to use a qualitative approach with the type of research is descriptive type. Data collection techniques in this study used three techniques consisting of observation, interviews and documentation. The result of this research is the implementation of the Tri Hita Karana concept has been applied in accordance with the three elements in it which meet the elements of organizational culture criteria and organizational culture function elements.